The vaccinia virus 14-kilodalton fusion protein forms a stable complex with the processed protein encoded by the vaccinia virus A17L gene. - Rodriguez, D (1993)
The mechanism by which the 14-kDa fusion protein of vaccinia virus (VV) is anchored in the envelope of intracellular naked virions (INV) is not understood. In this investigation, we demonstrate that the 14-kDa protein interacts with another virus protein with an apparent molecular mass of 21 kDa. Microsequence analysis of the N terminus of the 21-kDa protein revealed that this protein is encoded by the VV A17L gene. The 21-kDa protein is processed from a 23-kDa precursor, by cleavage at amino acid position 16, at the consensus motif Ala-Gly-Ala, previously identified as a cleavage site for several VV structural proteins. The 21-kDa protein contains two large internal hydrophobic domains characteristic of membrane proteins. Pulse-chase analysis showed that within 1 h after synthesis, the 14-kDa protein forms a stable complex with the 21-kDa protein. Formation of the complex was not inhibited by rifampin, indicating that the interaction between these two proteins occurs prior to virion morphogenesis. Immunoprecipitation analysis of disrupted virions showed the presence of the 21-kDa protein in the viral particle. Release of the 14-kDa-21-kDa protein complex from INV required treatment with the nonionic detergent Nonidet P-40 and a reducing agent. The protein complex consisted of 14-kDa trimers and of 21-kDa dimers. Since the 14-kDa fusion protein lacks a signal sequence and a large hydrophobic domain characteristic of membrane proteins, our findings suggest that the 21-kDa protein serves to anchor the 14-kDa protein to the envelope of INV.